2019
DOI: 10.1002/jat.3903
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological safety evaluation of a novel highly bioavailable turmeric extract formulation

Abstract: Turmeric (Curcuma longa L.) extracts have a long history of use worldwide, but a major limitation of these extracts is their extremely low oral bioavailability, caused by low absorption, rapid metabolism and rapid excretion following ingestion. Thus, a new highly bioavailable turmeric extract formulation (comprising turmeric extract, acacia gum, sunflower oil and quillaia extract) has been developed and is intended for use as a food ingredient. Safety of this novel extract was evaluated using the standard Tier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
(44 reference statements)
1
6
0
Order By: Relevance
“…[ 41 ]. In a toxicity evaluation experiment of a curcuminoid–essential oil complex (CEC) containing 95% curcuminoid, CEC showed no toxicity even at a dose of 5000 mg/kg [ 42 ], and a turmeric extract formulation (comprising turmeric) that was developed to increase bioavailability showed no side effects even at 3000 mg/kg of administration [ 43 ]. Therefore, our results suggest that the co-administration of curcumin or turmeric with amlodipine is safe and without side effects.…”
Section: Discussionmentioning
confidence: 99%
“…[ 41 ]. In a toxicity evaluation experiment of a curcuminoid–essential oil complex (CEC) containing 95% curcuminoid, CEC showed no toxicity even at a dose of 5000 mg/kg [ 42 ], and a turmeric extract formulation (comprising turmeric) that was developed to increase bioavailability showed no side effects even at 3000 mg/kg of administration [ 43 ]. Therefore, our results suggest that the co-administration of curcumin or turmeric with amlodipine is safe and without side effects.…”
Section: Discussionmentioning
confidence: 99%
“…As a food agent, curcumin is recognized as "generally safe" by the Food and Drug Administration (FDA) (Phipps et al 2020) with an adequate daily intake value recommended of up to 3 mg per kg of body weight by Joint FAO-WHO Expert Committee Report on Food Additives (JEFCA) (Kocaadam and Şanlier 2017) and European Food Safety Authority (EFSA) (European Food Safety Authority 2014). Other investigations reported that this compound is safe for humans up to 12 g/day without any side effects (Lao et al 2006).…”
Section: Safety and Bioavailabilitymentioning
confidence: 99%
“…Photodynamic technology (PDT) is a novel non‐thermal sterilisation technology to inactive microorganisms via cytotoxic reactive oxygen species (ROS) produced by the non‐toxic photoactive compound (photosensitiser) after harmless visible light irradiation (Cossu et al ., 2021). Curcumin is a polyphenolic compound isolated from the traditional Chinese herbal medicine‐turmeric (Rahman et al ., 2015), which has diverse biological activities and is recognised as a safe and non‐toxic natural food additive (Phipps et al ., 2020; Hou et al ., 2022). In recent years, curcumin has been widely used as a photosensitiser for PDT due to its good photosensitivity properties (Corrêa et al ., 2020; Seidi Damyeh et al ., 2020; Wang et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%